Obstacles Facing Inclusive Education in Kindergartens in Karak Governorate - Yahya Husain Othman Al-Qatawneh (دراسات: العلوم التربوية, 2022)
Objectives: This study aims to identify the obstacles facing inclusive education in inclusive kindergartens from the point of view of teachers and parents in Karak Governorate.